AHP Model for Selection of Sustainable Energy: A Focus on Power Generation and Supplying for End-users - Mohamad Faizal Bin Ahmad Zaidi; Shafini Binti Mohd Shafie; Mohd Kamarul Irwan Bin Abdul Rahim (International Journal of Supply Chain Management, 2020)
AHP is one of important technology management tools for decision making that is used during technology selection process, and applied prior to acquisition of a new technology. In the last decade, AHP was discussed by numerous studies, covering wide-variety of areas, focusing on many criteria and sub-criteria, for the purposes of selecting, allocating, evaluating, or benchmarking different alternatives of technology. The use of AHP for selecting the source of renewable energy as the alternative for the non-renewable source of energy is important, especially to the environmental conscious’ end-users, or those who are living in the rural area. However, in the field of sustainable energy, AHP application for power generation focusing on the end-users is still limited. As a result, this study aims to develop an AHP model, by investigating the suitable group of criteria, sub-criteria, and alternatives that will suit the needs of the end-users. This model will helps the relevant parties to identify the most suitable sources of technology for power generation to solve the end-users’ needs. To do this, secondary data were collected from the relevant empirical studies. Based on the descriptive analysis, it was found that the previous studies have ranked and prioritized each of these criteria, sub-criteria, and alternatives differently, which implies a specific AHP model for the end-users should be developed. With the findings, this study has developed an AHP model comprising of four major criteria, each with three sub-criteria, and five alternatives. This model is being verified by an ongoing research in Malaysia.